2022
DOI: 10.1016/j.amjcard.2021.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heart Rate and Rhythm on Corrected QT Interval During Paroxysmal Atrial Fibrillation

Abstract: Current knowledge on the dynamic changes of corrected QT (QTc) before, during, and after an atrial fibrillation (AF) episode is limited. It remains controversial which of the presently available formulas performs the best in calculating QTc during AF. This study was designed to explore whether an AF attack would affect QTc and to determine the performance of 6 available formulas in correcting QT before, during, and after AF. A total of 101 patients with Holter-documented paroxysmal AF were enrolled. QT interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(35 reference statements)
1
4
0
1
Order By: Relevance
“…This result is in full agreement with the results of previous authors, who demonstrated that the Bazett's formula produced the longest corrected QT in AF compared with other formulas, 4 that is an overestimation of the QTc during AF, 6 the most HR dependent 18,21,22 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result is in full agreement with the results of previous authors, who demonstrated that the Bazett's formula produced the longest corrected QT in AF compared with other formulas, 4 that is an overestimation of the QTc during AF, 6 the most HR dependent 18,21,22 …”
Section: Discussionsupporting
confidence: 92%
“…This result is in full agreement with the results of previous authors, who demonstrated that the Bazett's formula produced the longest corrected QT in AF compared with other formulas, 4 that is an overestimation of the QTc during AF, 6 the most HR dependent. 18,21,22 The most important clinical implication of this overestimation of the QTc during AF may be the choice of antiarrhythmic or anticancer drugs. Some patients are at risk of being undertreated with even vital medications for this overestimation of the QTc.…”
Section: T a B L E 2 Differences In Estimatedmentioning
confidence: 99%
See 1 more Smart Citation
“…The tangent method was used to define the end of the T-wave in the lead with the longest QT interval. All measured QT intervals were corrected for cardiac frequency using Fridericia's formula [ 10 , 11 ]. Prolongation of the QT interval was defined as a QTc interval ≥460 ms in females [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…QT should be corrected based on R‐R interval to eliminate heart rate effects on QT interval (Yu et al, 2022). Bazett (1997) created a formula for corrected QT (QTc) calculation approximately one century ago.…”
Section: Introductionmentioning
confidence: 99%